Next generation microalgae biodiesel: a strategy towards circular bioeconomy / Uganeeswary Suparmaniam, Yaleeni Kanna Dasan and Lam Man Kee - Suparmaniam, Uganeeswary; Dasan, Yaleeni Kanna; Lam, Man Kee (2022)
The present study investigates the potential of chicken compost as an alternative nutrient source to grow Chlorella vulgaris in batch bubble column photobioreactor system for lipid-based biofuel production. Experimental results showed that microalgae cultivated in chicken compost medium exhibited higher biomass concentration (1.0 g/L) as compared to the bold basal media (BBM). Additionally, it was shown that Chlorella vulgaris cultivated in recycled media produced biomass concentration that was similar to that of the fresh medium. Meanwhile, the carbon dioxide (CO2) fixation efficiency obtained in this study was 20% higher than those reported previously. Microalgae harvesting using biofloculant prepared from shell waste resulted in 99% flocculation efficiency without a negative impact on the lipid content. The fatty acid methyl ester (FAME) acquired comprised of two main alkyl groups namely, C16 and C18, which maintain the suitability of microalgae lipid for quality biodiesel production.